A molecular tool to identify Anastatus parasitoids of the brown marmorated stink bug. Issue 7 (17th July 2019) - Stahl, Judith M.; Gariepy, Tara D.; Beukeboom, Leo W.; Haye, Tim
Abstract: Globally, Anastatus species (Hymenoptera: Eupelmidae) are associated with the invasive agricultural pest Halyomorpha halys (Stål) (Hemiptera: Pentatomidae). In Europe, the polyphagous Anastatus bifasciatus (Geoffroy) is the most prevalent native egg parasitoid on H. halys eggs and is currently being tested as a candidate for augmentative biological control. Anastatus bifasciatus frequently displays behavior without oviposition, and induces additional host mortality through oviposition damage and host feeding that is not measured with offspring emergence. This exacerbates accurate assessment of parasitism and host impact, which is crucial for efficacy evaluation as well as for pre‐ and post‐release risk assessment. To address this, a general Anastatus primer set amplifying a 318‐bp fragment within the barcoding region of the cytochrome oxidase I (COI) gene was developed. When challenged with DNA of three Anastatus species — A. bifasciatus, Anastatus japonicus Ashmead, and Anastatus sp.—, five scelionid parasitoid species that might be encountered in the same host environments and 11 pentatomid host species, only Anastatus DNA was successfully amplified. When applied to eggs of the target host, H. halys, and an exemplary non‐target host, Dendrolimus pini L. (Lepidoptera: Lasiocampidae), subjected to host feeding, no Anastatus amplicons were produced. Eggs of the two host species containing A. bifasciatus parasitoid stages, from 1‐h‐old eggs to pupae, and emerged eggs yielded Anastatus fragments. Confirmation of parasitoid presence with dissections and subsequent PCRs with the developed primer pair resulted in 95% success for 1‐h‐old parasitoid eggs. For both host species, field‐exposed sentinel emerged eggs stored dry for 6 months, 100% of the specimens produced Anastatus amplicons. This DNA‐based screening method can be used in combination with conventional methods to better interpret host‐parasitoid and parasitoid‐parasitoid interactions. It will help address ecological questions related to an environmentally friendly approach for the control of H. halys in invaded areas. Abstract : In Europe, the polyphagous Anastatus bifasciatus (Hymenoptera: Eupelmidae) is the most prevalent native egg parasitoid of the invasive pest Halyomorpha halys (Hemiptera: Pentatomidae) and is being tested as a candidate for augmentative biological control. To assess parasitism levels and non‐target effects, a general Anastatus primer set amplifying a 318‐bp fragment within the barcoding region of the cytochrome oxidase I gene was developed. DNA of three Anastatus species was successfully amplified and 1‐h‐old A. bifasciatu s eggs were detected with 95% success.